(untitled) (Bioscience Journal, 2023)
Diarrhea remains a significant cause of death worldwide among children under five years old. In Brazil, the highest incidence of the disease occurs in the north region, and the epidemiological characteristics of diarrhea in Araguatins, TO, northern Brazil, have not been reported. The present study aimed to analyze the occurrence of acute diarrheal diseases (ADD) in Araguatins between 2014 and 2019 and its relationship with the quality of the public water supply. The study also analyzed the correlation between ADD frequency and rotavirus vaccination coverage of children. The data were obtained from the Brazilian Ministry of Health (SIVEP-DDA database) and the Health Surveillance Agency of Araguatins. The reported cases of acute diarrheal diseases significantly increased in 2018 and 2019 compared to the other years, and the occurrence of greater severity in the age group of ³10 years increased in the same period. The highest incidence of diarrhea occurred in 2018 when the application of rotavirus vaccines to children was the lowest. In most years investigated, the cases of acute diarrheal diseases occurred in both rainy and dry periods. However, in 2016, diarrhea cases were concentrated in the dry period, and Escherichia coli and total coliforms were found more frequently in the public water supply. The highest frequency of contamination with E. coli and total coliforms occurred in the Downtown area. The conclusion was that diarrheal disease may be caused, at least partially, by water-conveying agents in the treated public water supply of the Araguatins.